2019
DOI: 10.15406/ijh.2018.02.00131
|View full text |Cite
|
Sign up to set email alerts
|

Variability and trends of rainfall extreme events in north east highlands of Ethiopia

Abstract: This study was conducted in south Wollo to investigate the spatio-temporal variability of nine extreme rainfall indices and their trends. The daily rainfall was obtained from six meteorological stations in the period (1984-2014). Sen's slope estimator and Mann-Kendall's test were used to determine the magnitude and trends of changes, respectively. The results showed complex patterns of rainfall. Rainfall significantly (P<0.05) increased in summer in some of the stations (Dessie, Haik and Mekaneselam) and showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 28 publications
5
26
0
Order By: Relevance
“…The irrigation infrastructure periods. Similarly, no significant trend in annual rainfall has been reported in a number of studies for some stations in the Awash River Basin [14,[17][18][19]. On the other hand, Rosell [20] found an increasing trend in annual rainfall in six out of the seven stations in the Awash River Basin; whereas, Bekele et al [18] and Asfaw et al [21] reported a significant decreasing trend in annual rainfall over some stations in the basin.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…The irrigation infrastructure periods. Similarly, no significant trend in annual rainfall has been reported in a number of studies for some stations in the Awash River Basin [14,[17][18][19]. On the other hand, Rosell [20] found an increasing trend in annual rainfall in six out of the seven stations in the Awash River Basin; whereas, Bekele et al [18] and Asfaw et al [21] reported a significant decreasing trend in annual rainfall over some stations in the basin.…”
Section: Introductionmentioning
confidence: 90%
“…Linear regression is severely affected by outliers, missing data, and the starting and ending values of the time series [22][23][24]. However, linear regression based on ordinary least square (OLS)-based has been used for trend analysis in a number of studies [1,14,15,17,19,[25][26][27][28]. For the non-parametric tests, no assumption is made about the distribution of the population.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations